2020
DOI: 10.3897/natureconservation.40.51633
|View full text |Cite
|
Sign up to set email alerts
|

Polypores, Agrobacterium and ivy damage on Hungarian ancient trees

Abstract: Ancient trees are important habitats, confer vital ecological roles and function as cultural legacies. Old trees with large girth are keystone structures in various ecosystems. We aim to present which species amongst the greatest Hungarian trees (and some other phanerophyte plants) are damaged by polypores (the most important agents of wood decay), Agrobacterium tumefaciens (usually causing root tumour) or ivy (competing against the native vegetation and causing windthrow damage) and at what extent and frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Secondly, there were 18 unique species in GC, and then 17 unique species, including the nine counts of Juniperus procumbens (No. 19) Nine factors were selected to build an RDA model, which explained 84.1% of the total variation. In this model, axes 1 and 2 explained 84.06% and 15.94% of the total variance, respectively.…”
Section: Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, there were 18 unique species in GC, and then 17 unique species, including the nine counts of Juniperus procumbens (No. 19) Nine factors were selected to build an RDA model, which explained 84.1% of the total variation. In this model, axes 1 and 2 explained 84.06% and 15.94% of the total variance, respectively.…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Currently, the studies concerning urban ancient trees cover a variety of themes, such as field investigation [13][14][15], spatial distribution [7,16], rejuvenation and pest control [17][18][19], and protection legislation [20][21][22], as well as the aesthetic and spiritual aspects of ancient trees [23,24]. Among them, most studies have focused on species diversity and spatial differentiation [7,25].…”
Section: Introductionmentioning
confidence: 99%
“…Second, despite different definitions of heritage trees, investigation and monitoring method have certain similarities; thus, sophisticated and intelligent techniques, including unmanned aerial vehicles, have been widely used (Singh et al, 2015;Qiu et al, 2018). Finally, biologists and foresters primarily aimed to explore rejuvenation and pest control; thus, they conducted research on specific tree species (Zhang et al, 2013;Takács et al, 2020). Some studies have indicated that heritage trees are closely associated with daily needs of local residents and their cultures and beliefs, and the direct or indirect historical and cultural value of heritage trees has been effectively excavated (Jordan et al, 2021;Cannon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several natural events, such as lightning strikes, storms, insect infestations and epiphytic entwinement (Fig. 4c) also threaten the survival of LOGs (Yu and Gao 2004;Takács et al 2020;Wang et al 2020).…”
Section: Tree-habitat Types and Growth Status Of Logsmentioning
confidence: 99%